Insulin resistance in NSCLC: unraveling the link between development, diagnosis, and treatment - Zhan, Shizhang; Wang, Liu; Wang, Wenping; Li, Ruoran (Frontiers in Endocrinology, 2024)
Lung cancer is responsible for the highest number of cancer-related deaths, with non-small cell lung cancer (NSCLC) being the most prevalent subtype. A critical aspect of managing lung cancer is reducing morbidity and mortality rates among NSCLC patients. Identifying high-risk factors for lung cancer and facilitating early diagnosis are invaluable in achieving this objective. Recent research has highlighted the association between insulin resistance and the development of NSCLC, further emphasizing its significance in the context of lung cancer. It has been discovered that improving insulin resistance can potentially inhibit the progression of lung cancer. Consequently, this paper aims to delve into the occurrence of insulin resistance, the mechanisms underlying its involvement in lung cancer development, as well as its potential value in predicting, assessing, and treating lung cancer.